Metode penelitian bisnis / Donald R. Cooper ; alih bahasa, Widyono Soetjipto, Uka Wikarya - COOPER, Donald R; Emory, C. William; Sucipto, Widyono; Wikarya, Uka (Erlangga, 1998)
... jil. : ilus. ; 25 cm.